Feminism in God is A Woman MV: A Multimodal Critical Discourse Analysis - Gema Ariani Rahmawati; Ichwan Suyudi (Universitas Lambung Mangkurat, 2023)
Music as one of the largest media is used to influence audiences, which in this case is woman portrayal or feminism. Ariana Grande released a woman empowerement song and its music video entitled that portrays feminism. The goal of this study is to examine the portrayal of feminism in Ariana Grande's God Is a Woman MV. The data in this qualitative research is analyzed using Multimodal Critical Discourse Analysis (MCDA). The findings revealed that the God is a Woman MV symbolizes post-modern feminism ideology, as shown by Ariana as the primary character who has the freedom to express herself, full authority over her body, and the power or strength to confront patriarchy. Furthermore, the music video depicts radical feminism ideology by depicting woman superiority over man. Ariana impact audiences by messages given, which are a post-modern feminist concept and radical feminism ideology, through using music videos as a platform to influence audiences.